The two philosophers of the School of Athens (Revista do Tribunal Regional Federal da 3ª Região, 2017)
In the workroom of Pope Julius II (1443-1513), currently one of the most visited in the Vatican, is the fresco Stanza della Segnatura, the School of Athens, painted in 1510 by the Italian Renaissance painter Rafael Sanzio (1483-1520). One of the most powerful popes of the Catholic Church could have chosen a biblical scene for his workroom in search of inspiration when making decisions, but he opted for classical Greece, more precisely Greek philosophy. Composed with singular symmetry and balance, the School of Athens is a great example of how the Renaissance conceived the intellectual life of ancient Greece. Amid the perspective buildings of Athens, the most representative Greek philosophers are portrayed in an arrangement that excels in harmony and balance. In the center, the figures of Plato (426-347 BC) and Aristotle (384-322 BC) stand out. They seem to be debating. Plato, the elder, points his right hand upwards, while Aristotle points forwards and downwards. These gestures sum up the classic disagreement between the two philosophers: "Plato looks to the sky, the supposed heaven of ideas, Aristotle looks to the earth and rehabilitates sensitive experience". The gestures denote different conceptions of truth. The opposition between the two philosophers' visions permeates the history of philosophy to this day, especially political philosophy. In any political debate, no matter how simple, we always see the opposition between a more idealistic vision of what politics should be like and a more realistic one that seeks solutions based on how institutions actually work and not how they should work.
Keywords: School of Athens; Philosophers; Plato; Aristotle; Republic; Politics